Authors' reply to comment on "stability of fuzzy control systems with bounded uncertain delays". - Zhang Yi (IEEE Transactions on fuzzy systems)
For comment see ibid., p.285-6 (2004). The authors reply to a comment on their paper (Z. Yi and P.A. Heng, see ibid., vol.10, p.92-7, 2002) by agreeing with the comment.